Baicalin Induces a Potent Innate Immune Response to Inhibit Respiratory Syncytial Virus Replication via Regulating Viral Non-Structural 1 and Matrix RNA - Qin, Sheng; Huang, Xianzhang; Qu, Shaogang (Frontiers in Immunology, 2022)
Respiratory syncytial virus (RSV) infection is the most frequent cause of hospitalization in pediatric patients. Current systemic treatment and vaccines are not curative and re-infection is often associated with a more drastic incidence of the disease. Baicalin is a flavonoid isolated from Scutellaria baicalensis with potent anti-viral characteristics, namely against RSV. However, its precise mechanism of action remains unclear. Here, using in vitro methods and an in vivo murine model of RSV infection, we showed that baicalin inhibits RSV replication induces translational upregulation of type I interferons (IFNs), IFN-α and IFN-β, and reverses epithelial thickening in lung tissues. Moreover, baicalin inhibits transcription of the RSV non-structural proteins NS1 and NS2. Molecular docking and surface plasmon resonance-based affinity analysis showed that baicalin also binds to the α3 helix of the NS1 protein with an affinity constant of 1.119 × 10−5 M. Polysome profiling showed that baicalin inhibits translation of the RSV matrix protein (M) RNA. Baicalin mediates increased release of the ribosomal protein L13a from the large ribosomal subunit, where the extra ribosomal subunit L13a inhibits M RNA translation. These results comprehensively establish the multiple mechanisms by which baicalin induces a potent innate immune response against RSV infection.